Guidelines for mental health practice with clients who engage in sex work. Issue 3 (3rd July 2019) - Antebi-Gruszka, Nadav; Spence, Daniel; Jendrzejewski, Stella
Abstract: Many mental health practitioners have had or will have the opportunity to work with clients who engage in sex work (CSW). Sex work stigma is pervasive in the general population, and among mental health professionals, including sex and relationship therapists. Such stigma may lead to differential, unfair, and even unethical treatment of CSW. Although there is a clear need for best practice guidelines for mental health practice with CSW, no guidelines have been developed thus far. Therefore, drawing on feminist, multicultural, and sex-positive philosophies, this paper presents ten guidelines that are designed to: (1) address and increase mental health professionals' self-awareness of their own bias about sex work; (2) provide useful information about the multifaceted lived experience of CSW; and (3) offer culturally-appropriate counseling skills and intervention strategies in working with CSW. Acknowledging that multicultural competence is a professional process, rather than an outcome or an end, the guidelines included in this paper are developed with the underlying assumption that all mental health professionals are committed to be sex work-affirming and competent in working with CSW, regardless of therapeutic orientation. The guidelines discussed in this paper are informed by current literature about sex work and people who engage in it.